Exogenous HMGB1 Promotes the Proliferation and Metastasis of Pancreatic Cancer Cells - Zhu, Li; Ren, Shuai; Daniels, Marcus J.; Qiu, Wenli; Song, Lian; You, Tao; Wang, Dongqing; Wang, Zhongqiu (Frontiers in Medicine, 2021)
Abstract Background: Exogenous HMGB1 plays a vital role in tumor recurrence, and HMGB1 is ubiquitous in the tumor microenvironment. However, the mechanism of action is still unclear. We investigated the role of exogenous HMGB1 in tumor proliferation and metastasis using human SW1990 and PANC-1 cells after radiotherapy and explored the possible molecular mechanism. Materials and methods: Residual PANC-1 cells and SW1990 cells were isolated after radiotherapy. The supernatant after radiotherapy was collected. The relative expression of HMGB1 was evaluated by Enzyme Linked Immunosorbent Assay (ELISA). Electron microscope (EMS) was used to collect the images of pancreatic cancer cells pre and post radiotherapy treatment. The proliferation of pancreatic cancer cells which were treated with different radiation doses was measured by carboxy fluorescein succinimidylester (CFSE). The migration rates of pancreatic cancer cells were measured by wound healing assays. Subsequently, the expression of related proteins was detected by Western Blot. In vivo, the subcutaneous pancreatic tumor models of nude mice were established, and therapeutic capabilities were tested. Results: HMGB1 was detected in the supernatant of pancreatic cancer cells after radiotherapy. The results of CFSE showed that exogenous HMGB1 promotes the proliferation and metastasis of pancreatic cancer cells. The western blot results showed activation of p-GSK 3β and up-regulation of N-CA, Bcl-2, and Ki67 in response to HMGB1 stimulation, while E-CA expression was down-regulated in pancreatic cancer cells in response to HMGB1 stimulation. In vivo, ethyl pyruvate (EP, HMGB1 inhibitor) inhibits the growth of tumors and HMGB1 promotes the proliferation of tumors after radiation. Conclusion: Radiotherapy induces HMGB1 release into the extracellular space. Exogenous HMGB1 promotes the proliferation and metastasis of PANC-1 cells and SW1990 cells by activation of of p-GSK 3β which is mediated by Wnt pathway.